Morphine and microRNA Activity: Is There a Relation with Addiction? - Rodriguez, Raquel E. (Frontiers in Genetics, 2012)
When we talk about drug addiction, we are really dealing with an extremely complex system in which there still remain many unknowns and where many empty spaces or missing links are still present. Recent studies have identified changes in the expression profiles of several specific miRNAs which affect the interactions between these molecules and their targets in various illnesses, including addiction, and which may serve as valuable targets for more efficient therapies. In this review, we summarize results which clearly demonstrate that several morphine-related miRNAs have roles in the mechanisms that define addiction. In this regard, morphine has been shown to have an important role in the regulation of different microRNAs, such as miR-let7 (which works as a mediator of the movement of the mu opioid receptor (MOR) mRNA into P-bodies, leading to translational repression), miR-23b (involved in linking MOR expression and morphine treatment at the post-transcriptional level), and miR-190 (a key post-transcriptional repressor of NeuroD). Fentanyl increases NeuroD levels by reducing the amount of miR-190, but morphine does not affect the levels of NeuroD. We also discuss the relationship between morphine, miRNAs, and the immune system, based on the discovery that morphine treatment of monocytes led to a decrease in several anti-HIV miRNAs (mir-28, 125b, 150, and 382). This review is centered on miR-133b and its possible involvement in addiction through the effects of morphine. We establish the importance of miR-133b as a regulatory factor by summarizing its activity in different pathological processes, especially cancer. Using the zebrafish as a research model, we discuss the relationship between mir-133b, the dopaminergic system and morphine, considering: (1) that morphine modulates the expression of miR-133b and of its target transcript Pitx-3, (2) the role of the zebrafish mu opioid receptor (zfMOR) in morphine-induced regulation of miR-133b, which depends o